Leptin levels in obese women with and without type 2 diabetes mellitus - Mehmet Akif Buyukbese; Ali Cetinkaya; Ramazan Kocabas; Aytekin Guven; Mehmet Tarakcioglu (Mediators of Inflammation)
INTRODUCTION: The role of leptin has been more clear in the endocrinology area after the discovery of its secretion from the adipose tissue. The aim of the study is to investigate the leptin levels in obese women in whom type 2 diabetes mellitus were present or absent.